Study of the Biologically Active Properties of Medicinal Plant Cotinus coggygria - Stanislav Sukhikh; Svetlana Noskova; Artem Pungin; Svetlana Ivanova; Liubov Skrypnik; Evgeny Chupakhin; Olga Babich (Plants, 2021)
The results of the studies have shown that to obtain an extract of a complex of biologically active substances of Cotinus coggygria, ethyl alcohol (mass fraction of alcohol 70%) with a hydromodule of 1:5 should be used, and the extraction should be carried out for 60 min at a temperature of 60 °C. The investigated plant extracts with the complex of bioactive substances from the Cotinus coggygria leaves and flowers are safe from the point of view of the content of heavy metals, pesticides, aflatoxin B1, radionuclides, as well as pathogenic and opportunistic microorganisms. It has been established that the Cotinus coggygria extract contains rutin, hyperoside, ferulic acid, quercetin, kaempferol, disulphuretin, sulphurein, sulphurein, gallic acid, methyl gallate, pentagalloyl glucose, 3,3′,4′,5,6,7-hexahydroxyflavonone, 3,3′,4′,5,5′,7-hexahydroxyflavonone, 3-O-α-L-rhamnofuranoside, 3,3′,4′,5,5′,7-hexahydroxyflavulium(1+), 7-O-β-D glucopyranoside, and 3,3′,4′,7-tetrahydroxyflavonone. The tested extracts have anticancer, antigenotoxic, and antimicrobial (against E. coli, S. aureus, P. vulgaris, C. albicans, L. mesenteroides) properties. The high antioxidant status of the tested extracts was established; the antioxidant activity of the samples was 145.09 mg AA/g (AA—ascorbic acid).